2004
DOI: 10.14748/bmr.v15.102
|View full text |Cite
|
Sign up to set email alerts
|

The milky spots of the peritoneum and pleura: structure, development and pathology

Abstract: The milky spots (MS), originally described by Ranvier as taches laiteuses, are found on the greater omentum but also in other peritoneal regions, as well as on the pleura and pericardium. They represent aggregations of mesenchymal tissue surrounding blood vessels. These small whitish regions are covered by mesothelium, and within the mesothelial layer are scattered macrophage-like cells. The blood supply of MS is provided by arterioles that give rise to capillary network formed by fenestrated or continuous end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
11

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 121 publications
(193 reference statements)
0
13
0
11
Order By: Relevance
“…Surprisingly, few studies have investigated its structural organization in dogs. Most publications rely on information gained in humans or laboratory animals, or on the findings in similar structures such as the pleura or the peritoneum (Michailova and Usunoff, ). As it is important to know the very basic composition of an organ to understand its underlying working mechanisms, the current study was performed to unravel this mystery.…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, few studies have investigated its structural organization in dogs. Most publications rely on information gained in humans or laboratory animals, or on the findings in similar structures such as the pleura or the peritoneum (Michailova and Usunoff, ). As it is important to know the very basic composition of an organ to understand its underlying working mechanisms, the current study was performed to unravel this mystery.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, these studies should investigate the (synaptic) relation of sympathetic nerve fibres to various OMS cell types such as immune and stromal cells, as well as the presence and type of adrenergic receptors on these cells. Although the current study focused on MSs in the greater omentum, similar structures, often referred to as extraomental MSs, can be found in the peritoneum, mesenterium, mediastinum, pericardium, and pleura (Michailova & Usunoff, ; Cruz‐Migoni & Caamano, ). As these structures are involved in local immune activity (Cruz‐Migoni & Caamano, ), including them in future studies is recommended.…”
Section: Discussionmentioning
confidence: 99%
“…OMSs are cellular aggregates of macrophages, B-cells, and T-cells (Shimotsuma et al 1991;Liu et al 2015). They develop during ontogeny (Krist et al 1997), are found in various animal species including humans (Michailova & Usunoff, 2004), and can be observed in large fixed omental tissue samples after staining with haematoxylin (Schurink et al 2019) (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fax: +90 2562470720. Email: ueren@adu.edu.tr, ulkereren@hotmail.com 1995, Van Vught et al 1996Michailova & Usunoff 2004).…”
Section: Introductionmentioning
confidence: 99%